Paget's Disease. Special Variety of Breast Cancer. A Case Report - Masleidy Valladares Valle; Tahimí Conde Cueto; Nery María Díaz Yanes (Medisur, 2012)
Paget's disease is a special variety of breast cancer. It is a rare disease that represents 1 to 3% of all breast cancers and is clinically characterized as an eczematous lesion on the nipple, later progressing to the areola surface and terminal lactiferous ducts. We present the case of a 48 years old female patient who attended consultation because of discoloration, eczema and depression of the nipple. Skin retraction and retroareolar palpable tumour were found. Through mammography, asymmetry was observed in the density of right mammary parenchyma in respect to the left retroarelar. It had a tumoural appearance. The biopsy was positive for Paget cells and invasive ductal carcinoma. As rare as this case is, we decided to have it published.